Suitability of Demand Response Program Equipped with Solar Energy in UTHM - N A Jefry; N A Zambri (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Demand Response Program (DRP) is a program developed in western country to cater high load demand. This system enhance the quality of the current smart grid system. This program encourage two-ways interaction between the consumer and the utility provider. The consumers are required to reduce their load consumption upon request by the utility provider, thus avoiding them from paying for the high load demand. However, the current design of DRP is seem to put the user at disadvantages. Thus, deployment of the new practice equipped with renewable energy sources will make the system more user- friendly. As DRP prove to be beneficial in many terms, this project is conducted to find DRP relevancy to be implemented in Universiti Tun Hussein Onn Malaysia (UTHM). According to the electrical consumption data disclosed by Facility Management Division, the power consumed by UTHM is remarkably high especially during 11.00 am to 12.00 pm. Thus, DRP is being proposed to be put into practise during this period. Nonetheless, it is not economically wise to implement the program to the whole campus. Therefore, three buildings with the most power consumption had been chosen for this study. They are the library, Faculty of Civil and Environmental Engineering (FKAAS) building and Faculty of Technology and Vocational Education (FPTV) building. The building power consumption and economic evaluation had been analysed using HOMER simulation. From the analysis, the combination of FPTV and FKAAS had been chosen for DRP implementation. The reason are, these buildings have superiority over the library in term of reliability and effectiveness. In terms of economy, it is almost equivalent to each other.